Experimental study on hydrate saturation evaluation based on complex electrical conductivity of porous media - Xing, Lanchang; Niu, Jiale; Zhang, Shuli; Cao, Shengchang; Wang, Bin; Lao, Liyun; Wei, Wei; Han, Weifeng; Ge, Xinmin; Wei, Zhoutuo (Elsevier, 2021)
The hydrate saturation is a critical parameter in the evaluation of gas hydrate reservoirs. The complex characteristics of hydrate-bearing sediments pose challenges to the reliability of conventional geophysical techniques for hydrate saturation evaluation. In this paper, we present a study on developing a novel approach to characterize the electrical properties of hydrate-bearing porous media and to evaluate the hydrate saturation quantitatively based on parameters of the complex electrical conductivity. In the laboratory experiments we prepared samples with the tetrahydrofuran hydrate forming in sands to simulate the hydrate-bearing sediments and for measuring the complex conductivity at frequencies from 20 Hz to 100 kHz. The frequency-dispersion characteristics of complex conductivity of the hydrate-bearing samples with different saturations were analyzed, and then three types of hydrate-saturation evaluation models, denoted as the conductance-based, polarization-based and fusion models, were developed based on the in-phase conductivity, frequency-dispersion characteristic parameters of the phase angle and the combination of those two, respectively. A critical frequency (fc = 2 kHz) can be identified, where both the phase angle and imaginary component of the complex conductivity reach their minima. The Archie's formula shows its capability to model the relationship between the in-phase conductivity and hydrate saturation (i.e., conductance-based model), but the frequency higher than fc is preferred because stable Archie parameters can only be obtained in that frequency range. Linear correlations between the hydrate saturation and frequency-dispersion characteristic parameters (i.e., the logarithms of FE (frequency effect) and slope of the relation between FE and FR (frequency ratio) of the phase angle can be obtained, serving as the polarization-based models in the frequency range higher than fc. The fusion model performs the best in the perspective of low errors and high reliability for predicting the hydrate saturation, because more parameters of the complex conductivity and underlying physics of the conductance and polarization have been incorporated. In the frequency range lower than fc in contrast to that of the phase angle, the quadrature conductivity shows remarkable frequency-dispersion characteristics with the variation of the hydrate saturation, showing the great potential for developing new saturation-evaluation models in future.
Keywords: Hydrate saturation; Complex electrical conductivity; Frequency dispersion; Conductance; Polarization; Information fusion